Isolation and characterization of a cDNA encoding a human liver/bone/kidney-type alkaline phosphatase. - Weiss, M J (1986)
Alkaline phosphatases (ALPs) [orthophosphoric-monoester phosphohydrolase (alkaline optimum), EC 3.1.3.1] isolated from human liver, bone, and kidney (L/B/K) exhibit very similar biochemical and immunologic properties that differentiate them from other human ALPs, such as those characteristically found in placenta and intestine. Despite their similarities, the L/B/K ALPs produced in different tissues show slight physical differences. To examine structural and evolutionary relationships between the various ALPs, a cDNA corresponding to L/B/K ALP mRNA has been isolated. A lambda 11 cDNA expression library was constructed using poly(A) RNA from the osteosarcoma cell line Saos-2 and screened with anti-liver ALP antiserum. The 2553-base-pair cDNA contains an open reading frame that encodes a 524 amino acid polypeptide with a predicted molecular mass of 57.2 kDa. This ALP precursor protein contains a presumed signal peptide of 17 amino acids followed by 37 amino acids that are identical to the amino-terminal sequence determined from purified liver ALP. In addition, amino acid sequences of several CNBr peptides obtained from liver ALP are found within the cDNA-encoded protein. The deduced L/B/K ALP precursor polypeptide shows 52% homology to human placental ALP and 25% homology to Escherichia coli ALP precursor polypeptides. Sixty percent nucleotide homology exists between the human L/B/K and placental cDNAs over the protein coding regions. The 5' and 3' untranslated regions of the L/B/K ALP cDNA, 176 and 805 base pairs, respectively, show no homology to the corresponding regions of placental ALP cDNA.